Residents' Perception of Cultural Activities as Quality of Life in Istanbul - Terzi, Fatih; Turkoglu, Handan Dulger; Bolen, Fulin; Baran, Perver Korca; Salihoglu, Tayfun (Springer, 2015)
Residents' perception of cultural activities is an important aspect of quality of life. This paper explores the association between the residents' perception of quality of life and their attendance in cultural activities. Firstly, we investigate the effect of the spatial distribution of existing cultural facilities on the level of attendance to cultural activities, and secondly, explore the relationship between the people's socio-economic structure and their level of attendance to culture related activities. A dataset of 1,635 dwelling units was selected through a systematic random sampling method for face-to-face interviews. Using surface modeling technique, a close relationship between the socio-economic structure and attendance to culture related activities was observed and the results show a need for a balanced spatial distribution of cultural facilities in the city. In addition, attendance to culture related activities should be increased and be more widespread through a balanced distribution of accessible activity nodes. This may help to improve the quality of life in Istanbul.
Keywords: Quality of life; Cultural activities; Spatial clustering; Istanbul